The Role of Maternal Clean and healthy living behavior in Preventing Stunting Among Toddlers - Widyaningsih, Tri Sakti; Wulandari, Novita Kurnia; Kanita, Maria Wisnu (Health Notions, 2026)
The causes of growth retardation are multifactorial and include family factors, maternal health, and nutritional status. Maternal knowledge of nutrition, childcare practices, and educational level are key determinants of child development. Poor maternal health and nutritional status increase the risk of developmental delays in children. Chronic malnutrition may lead to stunting, which can negatively affect long-term child development. This study aimed to determine the relationship between maternal clean and healthy living behavior and the incidence of stunting among toddlers in Banyuanyar Village. This study employed a quantitative analytical design with a cross-sectional approach. The population consisted of 56 mothers with toddlers, and total sampling was applied. Maternal clean and healthy living behavior was assessed using a questionnaire developed by the Indonesian Ministry of Health. Stunting was measured using anthropometric observations based on height-for-age (H/A) indicators. Data were analyzed using the Chi-square test. The Chi-square analysis yielded a p-value of 0.000, indicating a statistically significant relationship between maternal clean and healthy living behavior and stunting among toddlers in Banyuanyar Village. In conclusion, maternal clean and healthy living behavior is an important factor in supporting toddler health and preventing stunting. Consistent implementation of hygiene, sanitation, and proper childcare practices can help reduce the risk of growth disorders. Strengthening clean and healthy living behavior through continuous education and community-based interventions is essential to promote optimal child growth and development.Keywords: maternal; clean and healthy living behavior; stunting; toddler